Kaili Tribe Criminal Dispute Resolution Process from the Perspective of Customary Law in Central Sulawesi - Lubna, Lubna; Saptomo, Ade; Ibrahim, Metty Murni Wati; Situngkir, Rospita Rufina; Kristianto, Dhani (Syntax Corporation, 2024)
This research discusses customary law in Indonesia which is pluralistic because it reflects the diversity of tribes and ethnic groups. Customary law is still relevant and applicable in the life and culture of Indonesian society. Customary law as positive law has a special characteristic, namely that there is little written statute, despite its value applying in society. This research is descriptive in nature using normative analysis, literature studies, and field surveys. The research results show that customary law has a position that is recognized in statutory regulations, including the 1945 Constitution, the Human Rights Law, and the Draft Criminal Code. The implementation of traditional law is elucidated through the Kaili customary justice process in the Central Sulawesi region, with the stages of decision-making and the types of sanctions that can be given.